Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s11356-017-0446-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing mercury uptake by leaves of stone pine (Pinus pinea L.) in Almadén (Central Spain)

Abstract: The use of trees for biomonitoring of mercury (Hg) and other atmospheric pollutants is of increasing importance today. Leaves from different species have been the most widely used plant organ for this purpose, but only pine bark, and not leaves, was used to monitor Hg pollution. In Almadén (South Central Spain), the largest cinnabar (HgS) deposits in the world have been mined for over 2000 years to obtain metallic Hg and this activity has caused the widespread dispersion of this toxic element in the local envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…The potential leachable fraction of Hg (LHg) was tested on the soil and growing medium samples collected before/after plant cultivation in accordance with procedure described by Barquero et al LHg was extracted by the EPA 1312 method that is designed to determine mobility of both organic and inorganic forms of Hg . Thus, 5 g of solid sample was extracted in 100 mL of H 2 SO 4 /HNO 3 (60/40 m/m) mixture.…”
Section: Methodsmentioning
confidence: 99%
“…The potential leachable fraction of Hg (LHg) was tested on the soil and growing medium samples collected before/after plant cultivation in accordance with procedure described by Barquero et al LHg was extracted by the EPA 1312 method that is designed to determine mobility of both organic and inorganic forms of Hg . Thus, 5 g of solid sample was extracted in 100 mL of H 2 SO 4 /HNO 3 (60/40 m/m) mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Their detailed analysis of data registered in these sediments, including their precise dating, makes evident that the human activities developed in the area since the beginning of twentieth century have supposed an important increment of the presence of those pollutants in the regional environment; besides, and being the studied accumulations susceptible of erosive processes, they still represent a risk for the future of the area. The presence of mercury in Almadén (Castilla-La Mancha region of Spain) is well known, and the environmental consequences of this fact have been described in a large number of publications; however, Barquero et al (2018) present a novel methodology to quantify the atmospheric contamination related with the fact that this element has a high volatilization potential, being present in the atmosphere of areas in which there is no active sources of direct release of the element to the atmosphere, which is the case for this area after the cessation of mining and metallurgy and the reclamation of the mine's main dump (Tejero et al 2015). In particular, these authors use the bioaccumulation capacity of needles of stone pine to biomonitor the mercury presence in the atmosphere.…”
Section: Environmental Quality Monitoringmentioning
confidence: 99%
“…In the terrestrial environment, these Hg compounds are preferentially found in soils, bound to organic matter, as a product of atmospheric deposition (Si and Ariya 2018). Vegetation plays an important role in the Hg exchange process between the soil and the atmosphere, with Hg acquired from the soil via the roots (Liu et al 2017;Ahammad et al 2018) and from the atmosphere via the leaves (Kowalski and Frankowski 2016;Zheng et al 2017; Barquero et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Plants act as a temporary sink for Hg, and they provide a transfer pathway from the soil to the atmosphere or from the atmosphere to the soil via litterfall. It has been established in numerous studies that direct Hg uptake by plants from the soil is minor compared to the Hg emission/deposition direct from the atmosphere (Assad et al 2016; Kowalski and Frankowski 2016;Zheng et al 2017;Higueras et al 2016; Barquero et al 2019;Esbrí et al 2018). A great deal of effort has been devoted to clarifying gaseous elemental Hg (GEM) fluxes from the soil to the atmosphere, with a global cycle of net emissions reported in warm seasons and negligible flux in colder periods (Sommar et al 2012;Demers et al 2013).…”
Section: Introductionmentioning
confidence: 99%